The characteristics of consumer attitudes in the food market in Hungary - Soós, Mihály; Szabó , Sára; Szakály , Zoltán (Applied Studies in Agribusiness and Commerce, 2014)
The objective of our research was to examine the health status and health behaviour of the Hungarian population in relation of food consumption by identifying relationships between the underlying factors. In our research we used the objective factors from secondary data concerning nutritional status and body image as a framework for the interpretation of the examined relationship of eating attitudes and body attitudes. We chose survey as our test method, it was carried out on a national representative sample of 1000 people. After the examination of the factor structure of the two attitude measuring questionnaire, five consumer groups have been identified by the cluster analysis. The five clusters are: Uncontrolled Impulse Eaters, Dissatisfied Tense, Uninterested, Overweight Impulse Eaters and Conscious Consumers. This segmentation based on eating attitudes and body attitudes could serve as a guidance for health marketing experts and the manufacturers of health protective food to determine and address their target group.